Evaluasi Pengembangan Objek Wisata Hutan Pinus Buntudatu Kecamatan Mengkendek Kabupaten Tana Toraja - Astuti Anna Beka’; Fabiola B. Saroinsong; Josephus I. Kalangi (Sam Ratulangi University, 2022)
The tourist attraction of the Buntudatu pine forest, Mengkendek District, Tana Toraja Regency is an open nature tourism object of limited production forest managed by the Buntudatu Village Owned Enterprise (BUMDes) as a place for activities such as recreation, camping, relaxing. The purpose of this study was to describe and evaluate the potential development of the Buntudatu pine forest tourism object based on the observations and perceptions of visitors. The variables observed were the attractiveness, accessibility and infrastructure of the Buntudatu pine forest tourism object. Data collection methods were carried out through observation and distributing questionnaires to visitors who were found in the tourist area of Buntudatu pine forest as many as 36 respondents. The data obtained were analyzed based on the assessment of ODTWA (Objects of Natural Tourist Attraction) and the Likert scale. The results showed that based on the ODTWA assessment, the potential development of tourism objects in the Buntudatu pine forest area obtained an attractiveness value of 750 in the medium category, accessibility with a total score of 450 in the high category and infrastructure facilities a total score of 300 in the high category. Based on the visitor's perception of attractiveness, it is categorized as good with a score of 72.66%, accessibility has a good category value with a score of 68.69% from respondents, facilities have a good value with a value of 66.66% and tourist activities get a very good score of 100%.